Agroforestry Practices Contribution Towards Socioeconomics: A Case Study of Tawau Communities in Malaysia - Fazilah Musa; Nor Asyirah Lile; Diana Demiyah Mohd Hamdan (Biotechnical Faculty of the University of Montenegro, 2019)
Agroforestry is a key indicator in terms of socioeconomic level towards developing countries especially to rural communities for sustainable development. Generally, agroforestry practices are valued environmentally, economically and socially. However, a key problem within recent literatures in relation to agroforestry practices is lack of awareness and knowledge among local community in rural areas. The aim of this study was to identify the contribution of agroforestry practices towards socioeconomics of communities in Merotai Besar, Tawau, Sabah, Malaysia. The data collection was conducted by questionnaire, which was randomly distributed to 250 respondents from five (5) villages namely Merotai Besar, Simpang Tiga, Kijang, Langsat and Iban. Majority of respondents strongly agreed that agroforestry practices could provide food resources for the wellbeing of rural communities. More than half of the communities in Merotai Besar area practiced Agri silvicultural system. A small number of residences in the study area also practiced agrosilvopastoral and silvopastoral systems. In spite of the fact that 93.2% of respondents were practicing agroforestry, they lack awareness that they were practicing agroforestry. This was due to poor dissemination of agroforestry information. This paper suggests that policy makers should encourage stakeholders to provide training and skills development centre to enhance the community’s knowledge. Furthermore, it is necessary to encourage active community-based management practices within respective villages for sustainable economic development and to ensure prosperity for all. In conclusion, agroforestry practices can expand the socioeconomics level to reduce poverty of rural communities in Tawau area.